Uncertainty : Masa Depan Pendidikan Guru : Ditinjau Dari Perspektif Mahasiswa Calon Guru - Menik Kurnia Siwi; Sri Arita (Universitas Negeri Padang, 2026)
Uncertainty is part of the ever-changing education system. Change demands that educational institutions, teachers, and students adapt quickly. This study aims to examine the perspectives of prospective teacher students on uncertainty and the future of their teaching careers. A survey method was used to explore students' perspectives, opinions, and experiences regarding the teaching profession. The results are presented qualitatively using three main research themes: theory, mental health, and learning strategies. The study found that students understand that they constantly face uncertainty, must be able to find solutions to deal with uncertainty, and recognize that they chose to become teachers and understand the characteristics of that career. Based on the results, further research is recommended to identify opportunities for uncertainty in education and concrete ways to address uncertainty, such as through the development of a specialized curriculum in higher education.